Purification of glycolytic product from polyethylene terephthalate (pet) waste by a two-stage evaporation process - Goh, Hui Wen (2012)
Malaysia is a developing country. With the rise in income and standard of living together with the rate of industrial growth in Malaysia, the demand of materials will keep increasing. This directly increases the amount of waste generated. In Malaysia,almost all type of solid wastes are disposed off into landfill sites. Due to the limitation of the available landfill sites, many solutions are introduced by the Malaysia government to reduce the solid wastes being dumped to the landfill. Polyethylene terephthalate (PET) bottle is one of the plastic solid wastes that can be easily found in Malaysia. One of the solutions that can be used to solve the abundant of PET wastes is chemical recycling of PET wastes to produce other value added product. This method not only can decrease the PET waste in landfill sites but also can produce many useful recycled PET products. This research is focusing on the purification processes used in chemical recycling of PET waste. Crystallization and two stages evaporation processes were selected to purify the contaminated bis(2-hydroxyethyl) terephthalate (BHET) obtained from glycolysis of PET waste. This research was divided into two parts: first part was simulation of the two stages evaporation and crystallization processes using ASPEN PLUS to investigate the effect of operating temperature and pressure of two stages evaporation toward the percentage of ethylene glycol (EG) removed, heat duty needed and percentage of BHET recovered. Based on the simulation findings, the first stage evaporation was simulated at pressure range of 130 Pa to 10,000 Pa and temperature range of 90 °C to 180 °C while the second stage evaporation was simulated at pressure range of 50 Pa to 250 Pa and temperature range of 120 °C to 180 °C. The crystallization was simulated at temperature range of 5 °C to 30 °C to study the effect of crystallization temperature toward the percentage of BHET recovered. The second part of the research was verification of simulation result by conducting experiments using conventional crystallization and two stages evaporation processes. The ASPEN PLUS simulation results showed that increasing the operating temperature and decreasing the operating pressure of the two stages evaporation might increase the percentage of EG removed and at the same time increased the heat duty required and reduced the percentage of BHET recovered. The optimum conditions was selected based on higher EG removed with lower heat duty needed and higher BHET recovered. Optimum conditions of first and second stage evaporation were 105 °C and 1000 Pa and 130 °C and 50 Pa respectively. Two stages evaporation process was capable to reduce the composition of EG in glycolyzed mixture from 77 % to 0.15 % while increase the composition of BHET from 19 % to 82.48 %. Crystallization process using second purification route at 1 °C, with ratio of water used to glycolyzed solid of 5:1 and 3 hours cooling time was capable to remove EG yielding white crystallized solid consists of 93.02 % BHET. This shows that both methods can be used to purify glycolysis product.